The extant species of the genus Omma Newman and description of Beutelius gen. nov. (Coleoptera: Archostemata: Ommatidae: Ommatinae) - Escalona, Hermes E.; Lawrence, John F.; Ślipiński, Adam (Zootaxa, 2020)
The genus Omma Newman (type species Omma stanleyi Newman) is revised and redefined based on extant species, with examination of additional fossil species. As a result, only the species O. stanleyi Newman is retained in Omma and a new genus, Beutelius gen. nov. (type species Omma mastersi MacLeay), is described to accommodate the remaining Australian species: B. mastersi (MacLeay), comb. nov., B. sagitta (Neboiss), comb. nov. and B. rutherfordi (Lawrence), comb. nov. A new species, Beutelius reidi sp. nov., is described from Melville Range Nature Reserve in New South Wales, Australia. Diagnoses and new records for extant Ommatinae, including the male of B. sagitta and female of B. mastersi, are provided, as well as a key to extant genera and species.